ВЕКУА-ЭРДЕЙ-ЛОУНДЕС ТИПИДАГИ ЯНГИ АЛМАШТИРИШ ОПЕРАТОРЛАРНИ ҚУРИШНИНГ БИР УСУЛИ ҲАҚИДА (Scientific journal of the Fergana State University, 2023)
In this article the composition of the transformation operator Vekua-Erdey-Loundes with Bessel function in the nucleus and the fractional  order operator Reeman-Zuivill is studied. As a result  a new  prevention with a degenerated hypergeometric function Gumbert in the nucleus is recieved.